1.
[tex]a) \ 4-\frac{3}{8} = 3\frac{8}{8} -\frac{3}{8} = 3\frac{5}{8}\\\\b) \ -3\frac{1}{8}+4\frac{5}{16} = -3\frac{2}{16}+4\frac{5}{16} - 1\frac{3}{16}\\\\c) \ 2,2:(0,8-\frac{1}{5}) = \frac{22}{10}:(\frac{8}{10}-\frac{1}{5}) = \frac{11}{5}:(\frac{4}{5}-\frac{1}{5}) = \frac{11}{5}:\frac{3}{5} =\frac{11}{5}\cdot\frac{5}{3} =\frac{11}{3} = 3\frac{2}{3}[/tex]
[tex]d) \ \frac{0,5:\frac{1}{8}+(-\frac{1}{4})^{2}\cdot4}{-3}=\frac{\frac{1}{2}\cdot8+\frac{1}{16}\cdot4}{-3} = \frac{4+\frac{1}{4}}{-3} = \frac{4\frac{1}{4}}{-3} = \frac{17}{4}\cdot(-\frac{1}{3})=-\frac{17}{12} = -1\frac{5}{12}[/tex]
2.
[tex]a) \ -3,45\cdot8 = -\frac{345}{100}\cdot8 = -\frac{69}{5}\cdot2 = -\frac{138}{5} = -27\frac{3}{5} = -27,6[/tex]
[tex]b) \ (-1,4)^{3} = (-\frac{14}{10})^{3} = (-\frac{7}{5})^{3} = -\frac{343}{125} = -2\frac{93}{125}[/tex]
[tex]c) \ -0,3\cdot(-\frac{1}{3})^{2} =-\frac{3}{10}\cdot\frac{1}{9} =-\frac{1}{30}[/tex]
[tex]d) \ -5,6:(-0,8) = -56:(-8) = 7[/tex]